Konsumsi bahan pangan sumber karbohidrat dl jawa tengah=Carbohydrate Source Foodstuff Consumption in Central Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The research identified the response of carbohydrate-source foodstuff consumption to price and income in rural and urban areas, which were devided into low, middle, and high income levels. The data was from National Social-Economic Survey in Central Java in 1999. There were 600 household samples in the analysis. Double natural logarithm regression and Tobit model were used in the analysis. Rice demand in general was inelastic. Cassava demand was inelastic except at low income household in rural area, demand of cassava was elastic. Ln rural area and middle income household in Central Java and middle income hosehold in rural area, sweet potato demand was elastic. Instant noodles demand in general was elastic. Substitution and complementary relationships among various kinds of foodstuff vary by food kinds, location, and income level. Rice was normal good. Cassava was Giffen good at high income household in urban area. At low income household in rural area, sweet potato was luxury good. And instant noodles was luxury good at low income household in rural and urban areas.